Early Life Socioeconomic Status Moderates Associations Between Objective Sleep and Weight-Related Indicators in Middle Childhood - Breitenstein, Reagan S. (Sleep Health, 2019)
OBJECTIVES: This study tested whether early socioeconomic status moderated links between objective and subjective sleep and weight indicators during middle childhood. DESIGN: The study design was cross-sectional but included data from earlier assessment points in the study. SETTING: Data were collected from families across the state of Arizona. PARTICIPANTS: Participants were 382 children recruited from birth records (49.5% female; M(age) = 8.47 years; 56.5% European American; 25.1% Latino; 25% living at or below the poverty line). MEASUREMENTS: Assessments included socioeconomic status at 12 months of age, and sleep and weight indicators at eight years. RESULTS: Longer sleep durations predicted lower body mass index and decreased odds of being overweight/obese across all children, regardless of socioeconomic background. For children from low socioeconomic backgrounds, longer sleep duration predicted lower percent body fat, greater efficiency predicted lower percent body fat and body mass index and smaller waist circumference, and more sleep problems predicted larger waist circumference. For children from low socioeconomic backgrounds, greater sleep duration and efficiency also predicted the lowest odds of being overweight/obese, and more sleep problems predicted the greatest odds of being overweight/obese. CONCLUSIONS: Early life may be a sensitive period that sets the stage for stronger links between sleep and weight indicators in middle childhood. Findings offer important information regarding the protective role of sleep in the promotion of health, as well as the negative consequences that may be stronger for children who experienced low early-life socioeconomic status.